Sanctions Signed by Disciplinary Boards on Police Officers in The Practice of Administrative Control: In the Light of The Corona Pandemic - Mahmoud Sabry Abdelaziz, Mohamed Abdelsalam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The judiciary monitors the administration appropriately oversight in normal circumstances, and police officers in the event of those circumstances are subject to a delusion in the matter of implementing the administrative and judicial quality control of some work pressures. Therefore, the knowledge of jurisprudence and the elimination of a set of principles governing the trial before the disciplinary councils can be summarized in five main points, which is a proportionate necessity The disciplinary penalty with the disciplinary offense is proportionate and does not contain exaggeration, and it is not permissible to punish the same violation twice according to the principle of the law which recognized that a person may not be punished for the same act twice, with the implementation of the principle of imposing the most appropriate penalty for the accused, so the person is not punished according to a canceled law and the lesson is always with the immediate effect of the law All this in light of the principle of legality of disciplinary sanctions, and that legitimacy requires the necessity of establishing the principle of gradual disciplinary sanctions, all in light of the provisions of Police Law No. 109 of 1971 AD, and subject to judicial oversight.